Chronic facial eczema in sheep: description of gross and histological changes in the liver and association with serum gamma-glutamyltransferase activity at the time of sporidesmin intoxication. Issue 2 (4th March 2021) - Munday, JS; Ridler, A; Aberdein, D; Thomson, NA; Griffiths, K
ABSTRACT: Aims: To determine the gross and histological changes developing in the liver of sheep 8 months after a single period of exposure to sporidesmin and to examine associations between the severity of gross and histological changes to the liver and the activity of gamma-glutamyltransferase (GGT) measured in serum in the sheep at the time of intoxication. Methods: A group of 50 Romney ewes grazing a mixed ryegrass/white clover pasture were accidentally exposed to sporidesmin for up to 5 weeks. Seventeen sheep showed photosensitisation and four were subject to euthanasia. The remaining sheep were moved to safer pasture and a blood sample collected and analysed for serum GGT activity. The sheep were slaughtered 8 months later. Livers were classified into grossly normal, moderately affected, or severely affected and histology performed to assess portal fibrosis, biliary hyperplasia, portal inflammation, and hepatocellular necrosis. Results: Serum GGT activity ranged from 59 to 1571 IU/L (reference range 32–70 IU/L). Thirteen of the 46 sheep developed clinical signs of facial eczema. However, at slaughter all except four sheep had grossly detectable changes to the shape of the liver including atrophy of the left lobe and the lateral part of the right lobe. Hypertrophy was typically limited to the medial part of the right lobe. In severely affected sheep the liver hypertrophy formed a nodular bulging mass. Changes in the liver shape were classified as severe in 25 and moderate in 17 sheep. Severely affected livers contained significantly more fibrosis than moderately affected livers (p = 0.001, Cliff's delta ( d ) = 0.68). While there was significantly greater fibrosis and biliary hyperplasia in the left than right lobes, histological changes were present throughout all samples taken of affected livers. Serum GGT activity taken during acute intoxication were correlated to subsequent fibrosis and biliary hyperplasia. Conclusions: Hepatic fibrosis develops in sheep after a single episode of sporidesmin intoxication, even in sheep with only mildly elevated GGT activity at the time of intoxication. Furthermore, the severity of the subsequent hepatic fibrosis was predicted by the degree of elevation of serum GGT activity during intoxication. Clinical relevance: More research is required to determine how the presence and severity of hepatic fibrosis affect animal production. However, if hepatic fibrosis does decrease production, the consistent development of fibrosis after sporidesmin ingestion reinforces the importance of avoiding exposure of livestock to sporidesmin. Abbreviations: GGT: Gamma-glutamyltransferase; d : Cliff's delta